Distributed Fiber Optic Sensing for Fracture Geometry Inversion Using All Time Steps Data - Shaohua You; Geyitian Feng; Xiaojun Qian; Qinzhuo Liao; Zhengting Yan; Shuqi Sun; Xu Liu; Shirish Patil (Sensors, 2025)
As an advanced real-time monitoring technique, optic fiber downhole sensing has been widely applied in monitoring fracture propagation during hydraulic fracturing. However, existing fracture shape inversion methods face two main challenges: firstly, traditional methods struggle to accurately capture the dynamic changes in strain rate and fracture shape during the propagation process, and secondly, they are computationally expensive. To address these issues, this study proposes a full-time-step fitting inversion method. By precisely fitting all time steps of fracture propagation, this method effectively overcomes the shape deviation problems often encountered in traditional methods and significantly reduces computational costs. Compared to conventional single-time-step inversion methods, our approach not only provides a more accurate representation of the spatiotemporal dynamics of fracture propagation but also avoids the risk of significant errors in fracture shape reconstruction. Therefore, the proposed inversion method holds substantial practical value and significance in fracture monitoring and sensing for oil and gas fields.